Implementation Of The Bsi Cash Management System (Cms) Product Innovation To Enhance The Competitiveness Of Sharia Banking Products (A Case Study At Bank Syariah Indonesia, Bengkulu Area) - Indah Kusuma; Nilda Susilawati; Kustin Hartini (International Journal of Economics, Business and Innovation Research, 2026)
Digital transformation has driven the Sharia banking industry to continuously innovate its products and services to enhance competitiveness amidst the increasingly fierce financial industry landscape. One innovation developed by Bank Syariah Indonesia (BSI) is the Cash Management System (CMS), a digital service designed to facilitate the effective, efficient, and secure management of financial transactions for institutional clients. This study aims to analyze the implementation of the BSI Cash Management System (CMS) product innovation, identify its contribution to enhancing the competitiveness of Sharia banking products, and examine the obstacles encountered during its implementation at Bank Syariah Indonesia, Bengkulu Area. The study employs a qualitative approach using a case study method. Data were obtained through observation, in-depth interviews, and documentation involving internal personnel at Bank Syariah Indonesia (Bengkulu Area) specifically Funding and Transaction Relationship Managers (FTRMs) as well as institutional clients using the CMS service. Data analysis was conducted using the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. The research results indicate that the implementation of the BSI Cash Management System (CMS) has made a tangible contribution to improving the effectiveness of institutional financial transaction management by enabling faster, more secure, accurate, and transparent transaction processes. CMS also strengthens Bank Syariah Indonesia's competitiveness by providing digital services that align with the needs of institutional clients. However, the implementation of CMS still faces several challenges, including low digital literacy among some users, limited service promotion, and the need for enhanced client support. Therefore, improving digital education, strengthening marketing strategies, and developing service features are crucial factors in optimizing the utilization of CMS as a Sharia banking product innovation.